Voluntary Corporate Disclosures by Indian Companies - Varghese, Roshna (Indian Journal of Finance, 2012)
This paper reports on voluntary disclosure practices of Indian companies in their annual reports. The quality of disclosure has been measured using an index of disclosure consisting of voluntary items that should appear in an ideal annual report. The researcher classified voluntary disclosures into three groups - financial, non- financial and strategic information. The intercompany variations in voluntary disclosure has been explained by a conceptual model consisting of corporate attributes like company size, profitability, extent of international operations and nature of industry. It was found that extent of disclosure is significantly and positively related to company size, profitability and international listing status.